STIGMA TERHADAP REMAJA DENGAN HIV/AIDS DI SYAIR SAHABAT FOUNDATION - anisa meliawati (Universitas Merdeka Madiun, 2022)
This research aims to find about stigma against youth with HIV/AIDS in Syair Sahabat Foundation. The research method used is qualitative. Data collection techniques through interviews, observation, documentation and literature study. The subject in this study were the head of Syair Sahabat Fondation, youth with HIV/AIDS and society near Syair Sahabat Foundation. The result in this research are: 1. Society stigma against youth with HIV/AIDS is because they scared of also being infected HIV/AIDS, lack of knowledge about HIV/AIDS, aducational background and society factor. The stigma that occurs is because society think that youth with HIV/AIDS are dangerous people an have different values than normal society and their also have vialated the norms that apply in society. 2. In facing the society stigma, young people with HIV/AIDS feel sad because of discrimination from society, however they still have fighting spirit and motivated to continue their life because they have support from their families.